The evolution of preferential trade under regional trade agreements: Has anything changed? - Rohini Acharya; Thakur Parajuli (World Trade Organization (WTO), 2025)
This paper examines the evolution of global merchandise trade, between 2010 and 2022, assessing the share of imports subject to regional trade agreements (RTAs). A key question for us is whether the share of merchandise trade subject to preferences has kept pace with the proliferation in RTAs. The paper finds that with the growing number of RTAs over the period, the share of the total volume of global imports involving RTA partners increased from 37% in 2010 to 52% in 2022. However, potential preferential imports between them under RTAs remained relatively stable, rising slightly from almost 17% in 2010 to 23% in 2022. Moreover, we find that on average 80% of global imports which do not fall under RTA preferences continued to dominate global merchandise trade between 2010 and 2022. Using tariff-line level import data for 157 customs territories and their RTAs, we find that, to a large extent, an increase in MFN duty-free imports globally has limited the scope of preferential imports under RTAs, highlighting the continued significance of MFN principles in international trade.
Keywords: F13; F14; F15; F53; 330; WTO; RTAs; Preferential Trade; MFN Trade